PENDIDIKAN KECERDASAN PERSPEKTIF AL QUR’AN DAN HADITS - Mahmud Fauzi Hamidy; Muhammad Nur; Anisaurrohmah (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2022)
Regarding the important element of human interaction with the physical and social environment, the Qur'an in a number of verses explains the importance of thinking about the universe and social life to gain knowledge about it which in turn can instill and increase faith in Allah SWT the Creator. In terms of intelligence in the element of human success in achieving goals, the Qur'an explains the main purpose of human life in the world is to serve or obey Allah SWT. This goal certainly does not prevent humans from determining good goals in their life in this world; even the Qur'an and Hadith remind people not to forget the importance of world affairs.